A Simulation of the Transient Self-heating Process in Dynamically Loaded Rubber-based Multilayers Reinforced Composites - Petrova, Iuliia; Larin, Oleksiy (NTU "KhPI", 2016)
The paper deals with an investigation of the transient process of heat generation and stabilization of temperature balance inside pneumatic tires during stationary rolling. The heat generation value have been obtained via integration of deformation over the cycles for each point of model. The function of heat generation rate have been created in each point based on previously defined cycles of deformation and experimentally obtained of loss modulus for materials. The temperature distribution of tire has been found within process of thermal stabilization.
Keywords: heat generation; pneumatic tire; cycles of deformation; transient thermal analysis